Tendências, silenciamentos e perspectivas das pesquisas brasileiras sobre questões sociocientíficas na educação em ciências - Macedo, Jéssica Carolina Paschoal de (2023)
Since its inception, the field of Studies on the relations between STS envisioned understanding the development of science and technology as a human construction, which suffers interference from social, economic and political interests. Thus, we assume that the approximation of these studies with science education is oriented towards social transformation and the socio-political formation of students, which has also resulted in the implementation of discussions on socio-scientific issues (QSC) in education, as well as in the elaboration of of academic works to disseminate these research data. That said, an in-depth analysis of the literature produced is essential, with the aim of understanding the development of this field and its marks on science research and teaching in our country. For this, we used a state-of-the-knowledge survey, so that the information was compiled in two stages: 1) Complete articles published in the Annals of national events in the area (ENPEC, ENEQ, EPEF and ENEBIO) and 2 ) Complete articles published in national journals evaluated as Qualis CAPES A1, A2 and B1 (2013-2016 Quadrennial), in the teaching area. Thus, through the constitution of these data, our analyzes point to the main trends in the field of studies on QSC in Brazil: the majority of production by researchers located in the south-southeast axis, a fact that has changed over the last few years due to the expansion of universities and the creation of graduate programs in the north, northeast and midwest regions of the country. As the main silencings found, we highlight the absence of references for the delimitation of the teaching methodology used, as well as with respect to what training is aimed at with the inclusion of QSC in teaching. Finally, from the analysis of these documents, we seek to contribute to a greater understanding of studies on QSC in Brazil, as well as deepen discussions on trends, silencing and emerging themes of this field of studies in our country.